Progressive failure analysis of tow-placed, variable-stiffness composite panels - C. S. Lopes (2007)
The past developments on tow-placement technology led to the production of machines capable of controlling fibre tows individually and placing them onto the surface of a laminate with curvilinear topology. Due to the variation of properties along their surface, such structures are termed variable-stiffness composite panels. In previous experimental research tow-steered panels have shown increased buckling load capacity as compared with traditional straight-fibre laminates. Also, numerical analyses by the authors showed that first-ply failure occurs at a significant higher load level. The focus of this paper is to extend those analyses into the postbuckling progressive damage behaviour and final structural failure due to accumulation of fibre and matrix damage. A user-developed continuum damage model implemented in the finite element code ABAQUS (R) is employed in the simulation of damage initiation and material stiffness degradation. In order to correctly predict the buckling loads of tow-steered panels under compression, it is of crucial importance to take into account the residual thermal stresses resulting from the curing process. Final failure of tow-steered panels in postbuckling is predicted to within 10%, difference of the experimental results. Curvilinear-fibre panels have up to 56% higher strength than straight-fibre laminates and damage initiation is also remarkably postponed. Tow-steered designs also show more tolerance to central holes than traditional laminates.